Cigarette smoking, chronic peptic ulceration, and pepsin 1 secretion. Issue 11 (November 1979) - Walker, V; Taylor, W H
Abstract : The relationship between the secretion of pepsin 1 (the most electronegative of the pepsins), and the smoking habits of 219 patients has been investigated. Significantly more cigarette smokers with peptic ulceration (72.5%) secreted pepsin 1 in greater than trace amounts after pentagastrin or histamine than did non-smokers with ulceration (51.2%). Differences of a similar order were found for men with duodenal ulcer, women with duodenal ulcer, and all patients with gastric ulcer, but the difference was statistically significant only for men with duodenal ulcer. Significantly more patients with peptic ulcer smoking six to 15 cigarettes/day secreted moderate or high concentrations of pepsin 1 than did heavier smokers or non-smokers. There was no significant association between cigarette smoking and pepsin 1 secretion among 74 patients without ulceration. Maximal acid output was not significantly related to smoking in any group studied. The findings add to the increasing body of evidence linking pepsins and pepsin 1 with the pathogenesis of peptic ulceration.